Agile Procurement Volume I: Adding Value with Lean Processes - Nicoletti, Bernardo (Springer International Publishing, 2018)
This book is the first of two volumes presenting a business model to add value through Procurement. Including several case studies of successful implementation, it demonstrates how the increasing complexity of the business environment requires a significant intervention on the management of processes and information within individual organizations and through inter-company relations. Agile Procurement presents the application of the Agile method which optimises and digitizes processes in order to reduce wastage and defects. As a method, tool and a culture aimed at effectiveness, efficiency and economy of organisations, agile procurement requires a change of paradigm. This volume examines these areas of improvement and presents best practice in improving processes. Each chapter of the book presents and substantiates the costs and benefits of process improvement through agile procurement. This is is seen as the integration of Lean Six Sigma and digitization.